The rural food environment and its association with diet, nutrition status, and health outcomes in low-income and middle-income countries (LMICs): a systematic review - Choudhury, Samira; Bi, Afrin Zainab; Medina-Lara, Antonieta; Morrish, Nia; Veettil, Prakashan C. (Springer, 2025)
"Background: The food environment consists of external and personal domains that shape food purchasing decisions. While research on food environments has grown rapidly within high-income countries (HICs) in response to increasing rates of overweight, obesity, and non-communicable diseases (NCDs), critical research gaps remain. The role of food environment on diet, health and nutrition has been understudied in LMICs. To date, there has not been a systematic review specifically focusing on rural LMICs. This systematic review aims to synthesize findings from studies examining the association between rural food environment domains and diet, nutrition and health in LMICs or effects of food environment interventions on these outcomes. Methods: Searches were conducted from 9 databases: Medline (PubMed), Embase (Ovid), Global Health (Ovid), PsycINFO (Ovid), EconLit (EBSCOhost), Web of Science (Social Science Citation Index), Scopus, CINAHL (EBSCOhost), and Applied Social Sciences Index and Abstracts (ProQuest) to identify studies published between 2000 and 2023 that reported associations between this/these dimensions with diets, nutrition or health outcomes. Both quantitative and qualitative studies that were published in English were included. Data extraction and quality appraisal was conducted independently by two authors, before the study findings were collated and summarized through a narrative data synthesis. Results: Nineteen eligible studies were identified from 9 databases covering 11 LMICs. The included studies employed quantitative (n = 12), mixed method (n = 6) and qualitative (n = 1) designs in the neighbourhood food environment. In this review, availability dimension of the external food environment featured most prominently, followed by accessibility, affordability, desirability, and convenience dimensions of the personal food environment. Food availability was positively associated with diet (n = 10), nutrition (n = 7) and health (n = 1). There was good evidence regarding associations between food accessibility, diet (n = 7) and nutrition (n = 3). We identified some evidence that food price and affordability (n = 8) were considered key barriers to achieving healthy diets. Desirability (n = 4) and convenience (n = 2) dimensions were also associated with dietary outcomes, although we found only a few studies. Only one South African qualitative study was identified which highlighted limited availability and accessibility to local supermarkets and surrounding informal fruit and vegetable vendors to be a barrier to expensive, healthy foods consumption. Finally, evidence regarding health outcomes, sustainability dimension, impacts of food environment interventions on relevant outcomes and interactions between food environment dimensions was missing. Overall, seven out of nineteen studies were rated as good quality, six were rated as fair and six were rated as poor. Conclusions: Future interventions should consider improving availability and accessibility of nutritious foods to improve public health nutrition in rural LMICs. Evidence from studies assessing the workplace, home, and school food environments, food environment interventions, sustainability dimension and other key dimensions of the external food environment such as prices, vendor and product properties and marketing and regulation is needed to identify effective interventions to address malnutrition in all its forms characterized by the coexistence of undernutrition, overnutrition, undernutrition and diet-related non-communicable diseases (NCDs)."